From sensory to positivist utilitarianism and back: the rehabilitation of naturalistic conjectures in the theory of demand - Ulrich Witt (Max Planck Institute for Research into Economic Systems, 2005)
Demand theory grew out of the revision of utilitarianism. The original, Benthamite program - based on a naturalistic, hedonic interpretation of behavior - was replaced by an abstract, subjectivist approach, a motivational mechanics. The implications - expressed exclusively in observable quantities, prices, and incomes - were developed in demand theory. The paper discusses major steps and consequences of the revision together with more recent partial revocations and attempts at reintroducing a naturalistic interpretation. The latter can be enhanced, it is argued, by integrating the (non-utilitarian) theory of wants, a long-standing, but currently much neglected, source of empirical reflections on the motivations of economic behavior.
Keywords: 330